Efficacy of Chlorantraniliprole 5DT against Yellow Stem Borer (Scirpophaga incertulas Walker) and Leaf Folder (Cnaphalocrocis medinalis Guenee) of Rice - , Saritha R; , Visalalakshi M; , Bhavani B (Archives of Current Research International, 2025)
Aim: An experiment was conducted to evaluate the bio-efficacy of Chlorantraniliprole 5DT at various doses compared to other chemicals for management of yellow stem borer and leaf folder in rice Study Design: Randomised Block Design with nine treatments and three replications Place and Duration of Study: Regional Agricultural Research Station, Anakapalle, Andhra Pradesh during 2020 and 2021. Methodology: Thirty days old seedlings of rice variety, RGL 2537 were transplanted with a spacing of 20 ×15 cm2 in a plot of 5×8 m2 and all agronomical practices recommended for the region were followed to raise the crop except for the plant protection measures for pests. Nine treatments(chlorantraniliprole 5DT @ 30 ga.i/ha, Chlorantraniliprole 5DT @ 40 ga.i/ha, Chlorantraniliprole 5DT @ 50 ga.i/ha, Chlorantraniliprole 5DT @ 60 gm a.i/ha, Chlorantraniliprole 5DT @ 70 gm a.i/ha, Chlorantraniliprole 0.4%GR @ 40 ga.i/ha, Fipronil 80%WG @ 50 ga.i/ha, Cartap hydrochloride 4%GR @ 10 ga.i/ha (chemical check) and untreated control) were imposed and the time of application was 15-25 days after transplanting and again after 20-25 days after the first application. Results: The results revealed that the treatment Chlorantraniliprole 5DT @ 70 ga.i. ha-1recorded 79.35 per cent reduction over control followed by Chlorantraniliprole 5DT @ 60 ga.i. ha-1which recorded 78.07 per cent reduction over control with regard to yellow stem borer. Similarly, with regard to leaf folder, Chlorantraniliprole 5DT @ 70 g a.i. ha-1recorded 96.35 per cent reduction over control followed by Chlorantraniliprole 5DT @ 60 ga.i. ha-1which recorded 95.62 per cent reduction over control. Highest yield was recorded in the treatment Chlorantraniliprole 5DT @ 60 ga.i. ha-1 (48.40 qha-1 during 2020and 51.22 qha-1 during 2021) which was followed by Chlorantraniliprole 5DT @ 70 ga.i. ha-1 (46.32 qha-1 during 2020 and 50.40 qha-1 during 2021). Conclusion: Chlorantraniliprole 5DT @ 70 gm a.i. ha-1 and Chlorantraniliprole 5DT @ 60 gm a.i. ha-1 were most effective in management of yellow stem borer and leaf folder in rice also recorded higher yield.